​​Real-time Controller and Interface for a PID Control Demonstrator​ - ​​Li​, ​​Jiayi​ (Cranfield University, 2025)
​​This paper reports on the redesign of a flight desk control demonstrator for teaching feedback control. The original system, limited by a basic Java interface and minimal controller functionality, was upgraded to improve usability and pedagogical value. The backend was re-implemented as modular firmware on an Arduino Nano, featuring a deterministic 2 ms sampling loop and support for both PID and PIV controllers. Robust host–device communication was achieved using a framed UART protocol. A new MATLAB App Designer GUI was developed with modular panels for controller tuning, real-time step response visualisation, tutorials, and data export. Results show that the system met technical and educational requirements, providing an interactive, reproducible, and extensible platform for control systems education.​
Keywords: Real-Time Embedded Control; PID and PIV Control; Control Systems; Education; MATLAB; App Designer; GUI; Arduino-Based Demonstrator; Human–Computer Interaction (HCI)